The Influence of Working Capital to Total Assets, Debt to Equity Ratio, Total Asset Turnover, and Net Profit Margin on Profit Growth in Pharmaceutical Sub-Sector Companies Listed on the Idx for the 2017-2021 Period - Erika Mirza Dewi (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to determine the effect of Working Capital to Total Assets (WCTA), Debt to Equity Ratio (DER), Total Asset Turnover (TAT) and Net Profit Margin (NPM) on Profit Growth in Pharmaceutical Sub Sector Companies on the IDX for the period 2017 – 2021 . This study uses a quantitative approach. The population used in this study are Pharmaceutical Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2017 – 2021 with a total of 9 companies. The sample used in this study used 9 companies with the Saturated Sampling method. The data analysis technique used in this study uses Multiple Linear Regression, Classical Assumption Test, Hypothesis Test, and Coefficient of Determination Test. Data processing in this study uses the IBM SPSS 26 for windows program. The results showed that partially Working Capital to Total Assets had no significant effect on Profit Growth, Debt to Equity Ratio had a significant effect on Profit Growth, Total Asset Turnover had a significant effect on Profit Growth and Net Profit Margin had a significant effect on Profit Growth. While simultaneously Working Capital to Total Assets, Debt to Equity Ratio, Total Asset Turnover and Net Profit Margin have a significant effect on Profit Growth.